Kajian Hukum Terhadap Kedudukan Uang Koin (Logam) dalam Pengembalian Transaksi Jual Beli yang digantikan dengan Permen - Sari, Liani; Mamonto, Andi Annisa Nurlia; Katjong, Revie Kurnia; Irsan, Irsan; A. Tuhumury, Harry; N. Imbiri, Raykuni (Universitas Ekasakti, 2023)
This diversion of cash back for consumer spending often occurs in supermarkets, minimarkets and small stalls and has become a phenomenon in society, consumers are on the weak side because they accept the candy as a replacement for their cash back without any other choice. Even though this seems trivial, consumers feel uncomfortable with this action and it is possible that consumers still need their money back and not everyone likes or needs this candy. The phenomenon that occurred was consumer complaints regarding the actions of shop, supermarket and minimarket businesses who replaced their change with candy. The change that is replaced with candy is change worth hundreds of Rupiah. This often happens because the value of hundreds of dollars is considered to have little material value so consumers don't pay much attention to it. The actions of shop, supermarket and minimarket businesses who replace change with candy constitute a violation of consumer rights. Consumer rights are regulated in Law no. 8 of 1999 concerning Consumer Protection (hereinafter referred to as UUPK). Candy is not a legal means of payment in Indonesia. Article 2 paragraph (2) Law No. 23 of 1999 which was then changed to Law No. 3 of 2004 which was then changed again to Law No. 6 of 2009 concerning Bank Indonesia (hereinafter referred to as UUBI) states that: